Employer branding in the most attractive companies in Portugal: a multiple case study - Pinto, Luís; Duarte, Alzira (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
In a highly competitive labour market, attracting and retaining the best talent available has become one of the main concerns of the human resources management of companies around the globe. With this increasing competition, it becomes essential for firms to distinguish themselves from all the others and develop a strategy that allows them to be understood as attractive to their potential and current employees. As a result, employer branding has been gaining popularity among the business world, with a growing number of companies adopting it as a strategy to attract the most talented job seekers. Taking into account the Portuguese labour market and the existence of rankings that award the most attractive companies for job seekers, it became relevant to understand if companies are using an employer branding strategy in order to be considered as one of the most attractive companies in the country. In this sense, the present study is supported by three research questions that emerged from the literature. Together, the research questions are structured in order to understand how employer branding is developed and managed, how the organizations manage their distinctive characteristics in order to be seen as an attractive employer, and how do firms measure the impact of an employer branding strategy in their management. The basis of the research of this study was built in a multiple-case study where people from six of the most attractive companies in Portugal were interviewed regarding the process of employer branding in their firm. All the interviews were carried out with current employees from the organizations in study, with the six interviewees having management positions inside the Human Resources Department of their companies. The content of those interviews was then analysed by the means of a content analysis in order to draw the answers to the research questions. As a result of the study, this work provides evidences that employer branding is a concept that is already present in the Portuguese labour market, although showing that it is not correctly implemented by all the companies who are currently using it as a strategy to attract talent. The incorrect application of this strategy was found to happen not only due to the communication of an idealized view of the company instead of the real employment experience, but also due to the lack of instruments to measure the effects of employer branding in the management of the company. Although being wrongly executed in some areas, in other elements of this strategy like the employer value proposition, it was possible to understand that companies are able to define distinctive factors from each other. In conclusion, it is possible to understand that employer branding is a strategy that, although being present in the Portuguese labour market, still has room for improvement in the future. This study also shows evidences that even the companies that are understood as the most attractive companies of the country are still able to optimize their process in order to have a stronger and more attractive employer brand in the market.